Source location impact on relative tsunami strength along the U.S. West Coast. Issue 7 (18th July 2015) - Rasmussen, L.; Bromirski, P. D.; Miller, A. J.; Arcas, D.; Flick, R. E.; Hendershott, M. C.
Abstract Tsunami propagation simulations are used to identify which tsunami source locations would produce the highest amplitude waves on approach to key population centers along the U.S. West Coast. The reasons for preferential influence of certain remote excitation sites are explored by examining model time sequences of tsunami wave patterns emanating from the source. Distant bathymetric features in the West and Central Pacific can redirect tsunami energy into narrow paths with anomalously large wave height that have disproportionate impact on small areas of coastline. The source region generating the waves can be as little as 100 km along a subduction zone, resulting in distinct source‐target pairs with sharply amplified wave energy at the target. Tsunami spectral ratios examined for transects near the source, after crossing the West Pacific, and on approach to the coast illustrate how prominent bathymetric features alter wave spectral distributions, and relate to both the timing and magnitude of waves approaching shore. To contextualize the potential impact of tsunamis from high‐amplitude source‐target pairs, the source characteristics of major historical earthquakes and tsunamis in 1960, 1964, and 2011 are used to generate comparable events originating at the highest‐amplitude source locations for each coastal target. This creates a type of "worst‐case scenario, " a replicate of each region's historically largest earthquake positioned at the fault segment that would produce the most incoming tsunami energy at each target port. An amplification factor provides a measure of how the incoming wave height from the worst‐case source compares to the historical event.